STRATEGI PENANGANAN ANAK KORBAN KEKERASAN SEKSUAL OLEH LEMBAGA PERLINDUNGAN ANAK PROVINSI BALI - Andreas, Pieter (Humanis; Volume 15. No.3. Juni 2016)
Child Protection Agency is an institution that specifically handle the problems of children, where the existence of the Child Protection Agency in the province of Bali as an answer that is expected to provide a way out for solving problems sexual violence against children and lead to empowerment. Based on the description above issues in the review in this study as follows: 1) profile Bali Provincial Child Protection Agency; 2) strategies were implemented in the handling by the Institute for the Protection of Children against sexual violence. This research was conducted in order to: 1) identify the profile Child Protection Agency in the province of Bali; 2) knowing the strategies applied in the handling by the Institute for the Protection of Children against sexual violence. This research was conducted using qualitative methods, which were analyzed with the theory put forward by Robert K. Merton manifest and latent functions that are arranged in a functionalist paradigma, and the theory put forward by Soerjono Soekanto about violence. The results of the study showed that the Child Protection Agency in the province of Bali on set by Decree of the Governor and the latest by SK Number. 1375/30-G / HK / 2014, which the Child Protection Agency became a partner of the local authorities, particularly the Department of Social Welfare / Social Service in an effort protection of children in the province of Bali while the District level, namely POKJA (working group) under the coordination of the Provincial child protection Agency Bali. Implementation of child protection undertaken Child Protection Agency province of Bali has a strategy and have measures in prevention and handling of the case, in proportion to the legislation in force which can be seen as in the prevention efforts undertaken Child Protection Institution of province Bali by socialization Undang-Undang Number 35 of 2014 to the public.
Keywords: LPA Prov. Bali, the handling of child victims of sexual violence